An Analysis of Students’ Competency in Applying Reading Strategies Based on the Metacognitive Awareness of Reading Strategy Inventory (MARSI) - S, Rini Septa Angraini. (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Reading is a foundational skill in English language learning, especially within English as a Foreign Language (EFL) context. This research investigates the reading strategy application of fourth-semester students at the English Education Department of IAIN Bukittinggi through the lens of the Metacognitive Awareness of Reading Strategy Inventory (MARSI). Employing a descriptive quantitative method, data were collected from 32 randomly selected students using the MARSI questionnaire. The results demonstrate that most students exhibit high competency in utilizing reading strategies, particularly problem-solving strategies. However, variability remains in the application of global and support strategies. The study supports the importance of metacognitive awareness and suggests targeted pedagogical interventions to optimize strategic reading practices in EFL education.